Pain intensity and psychological distress show different associations with interference and lack of life control: A clinical registry-based cohort study of >40,000 chronic pain patients from SQRP - Gerdle, Björn; Dragioti, Elena; Rivano Fischer, Marcelo; Ringqvist, Åsa (Frontiers in Pain Research, 2023)
Both chronic pain and depressive and/or anxiety symptoms are associated with negative impacts on daily living, including interference and lack of life control. However, little is known about how pain and psychological distress affect these impacts. The first aim was to assess how pain intensity, psychological distress, and social support interact with interference and lack of life control. A second aim was to investigate whether the strength of these relationships is moderated by the presence or absence of depression and/or anxiety. Relatively low correlation and explanatory power (R2=0.16) were found for the pain intensity-psychological distress relationship. Pain intensity had a stronger effect on interference than on lack of life control. The reverse was found for psychological distress – i.e., psychological distress seemed to have a higher negative influence on function than on interference. The underlying assumption of the causal relationship between pain intensity and psychological distress determined how strong pain intensity and psychological distress influenced interference and lack of life control. Social support showed very similar absolute significant correlations with interference and lack of life control. Interference and lack of life control showed relatively weak associations. The psychological distress level was a moderating factor for several of the paths investigated. A clinical treatment consequence of the low correlation between pain intensity and psychological distress may be that clinically treating one may not reduce the effect of the other. The relative importance of pain intensity and psychological distress on interference and lack of life control depends on the underlying assumption concerning the pain intensity-psychological distress relationship. Interference and lack of life control showed relatively weak associations, underscoring the need to clinically assess them separately. Social support influenced both impact constructs investigated. The cohort display heterogeneity and thus presence of definite signs of anxiety and/or depression or not was a moderating factor for several of the associations (paths) investigated. The results are important both for the assessments and the design of treatments for patients with chronic pain.